MODERN RADIOTHERAPY REGIMENS AND BIOMARKERS OF RADIORESISTANT RECTAL TUMOR CELLS - N. G. Vasilchenko; D. S. Kutilin; N. N. Timoshkina; D. S. Potyomkin; S. I. Poluektov; M. A. Gusareva; N. G. Kosheleva; K. I. Soldatova; A. Y. Maksimov; O. I. Kit; Yu. S. Sidorenko (Сибирский онкологический журнал, 2020)
Purpose of the study: a review of available data on various modern radiation therapy regimens and their effectiveness, as well as currently known markers of tumor radioresistance. Material and methods. We analyzed relevant publications available in the PubMed and cochrane Library databases between 1984 and 2019, 60 of which were used to write this review. Results. Rectal cancer is one of the most common cancers worldwide. Over the past decade, there has been a significant increase in the incidence of rectal cancer in economically developed countries. In Russia, colorectal cancer is the third most common cancer after lung, gastric and breast cancers. Preoperative radiation therapy followed by surgery is the preferred treatment method for rectal cancer. However, there are cases with no response to preoperative radiation therapy due to tumor cell radioresistance. Various radiotherapy regimens have been developed, differing in their effectiveness: the frequency of local recurrences, overall survival rate and quality of life of patients. cell radioresistance markers are also known. among them, there are genetic markers (changes in gene expression and micro-RNa, mutations) and proteomic markers (changes in protein expression), which can carry not only predictive value, but also be used as targets for therapy. Conclusion. Radioresistance is the major factor leading to the failure of radiotherapy and poor prognosis in patients with rectal cancer. at present, no molecular biomarkers for radiotherapy response prediction are in routine clinical use. Further research is needed to create an effective panel of molecular biomarkers and to improve personalized care for rectal cancer.